Field-scale evaluation of pesticide uptake into runoff using a mixing cell and a non-uniform uptake model. (December 2019) - Young, Dirk F.; Fry, Meridith M.
Abstract: The uptake of soil-applied pesticide by runoff was evaluated at the field scale (0.06–3.6 ha) by examining data from previous field studies and using two popular chemical-uptake models: a uniform mixing cell, in which runoff mixes uniformly to a set depth, and a non-uniform uptake model, where chemical uptake decreases exponentially with soil depth. Both uptake models were implemented through the field-scale Pesticide Root Zone Model (PRZM5), which includes an update for adjusting runoff uptake parameters. For the nonuniform model, we conceptualized runoff as a distribution of subsurface flow, which assisted in revealing that a large amount (81%) of runoff must bypass soil interaction to adequately simulate the field data, with the remaining runoff acting over about a 3-cm depth. Similarly, the mixing cell required a large amount (84%) of runoff bypass for proper simulation, with the remaining portion acting over a 0.75-cm depth. Highlights: Adequate simulation of chemical uptake into runoff requires that more than 80% of the runoff to be non-interactive. Robust parameters, suitable for field-scale simulation, were derived for runoff uptake models. Non-uniform uptake models are advantageous when complex initial distributions of chemical are a concern.